Health risk assessment of people living in urban slums of District Sonipat, Haryana - Mahender Singh; Manish Goel; Binod Kumar Behera; J S Punia (Wolters Kluwer Medknow Publications, 2016)
Background: Migration has led to development of slums. Slum area improvement and clearance act, 1956, slums have been defined as mainly those residential areas where dwellings are in any respect unfit for human habitation by reasons of dilapidation, overcrowding, faulty arrangements or lack of ventilation, light, sanitation or combination of these factors which are detrimental to safety, health and morals, thereby compromising health of people leading to morbidity and mortality. About 22 % of the total population reside in slums. Methods: 10% of total families residing in the slums were selected by systematic random sampling. First family was selected randomly and subsequently every 10th family was included in the study sample Results: 13.2% population was under 5 years of age, out of which 2.7% were infants and 3.5% of the population was above the age of 60 years. 60% of the children <5 years of age who were examined were undernourished as per weight for age. 70% of adult females and 75% of children aged <5 years were anaemic. Conclusion: The study found a large number of respondents living in overcrowded and insanitary conditions, basic amenities were not available in majority of the households and families. Antenatal care and immunization status of the beneficiaries were lacking.